Adoption of Voluntary Measures for Reducing Electricity Consumption in the REPowerEU Plan Context: A Romanian Consumer Perspective - Stelian Stancu; Anca Maria Hristea; Camelia Kailani; Denisa Elena Bălă; Andreea Pernici (Amfiteatru Economic)
Reducing energy consumption has important implications for the sustainable development of society, but this consideration has become more stringent in the actual geopolitical context. Following the strategic directions established by the European Green Pact and "NextGenerationEU", a concrete action of the European Commission was the elaboration of the REPowerEU Plan, which aims to make Europe independent from Russian fossil fuels before 2030 and transition to green energy. In this context, in order to know the attitude, behaviour and future intentions of Romanian consumers toward voluntary measures aimed at reducing energy consumption, quantitative marketing research was carried out, in which data collected through a questionnaire led to the identification of new factors that can influence energy saving behaviour: the level of information of household consumers and the level of perceived importance, compared to voluntary measures to reduce electricity consumption. Although the research results cannot be extrapolated to the level of the entire Romanian population, but only to certain segments, the authors consider the association of consumption behaviour with two important factors, which have not been analysed in the scientific literature so far, to be a success. This analysis is necessary to understand, improve, and align the actions of domestic consumers with the strategic plans of the European Union for the implementation of measures to reduce energy consumption.